The Tomato Pip's Story: Creative Narratives as Bridging Cultural and Science Discourses for Indigenous Students - Lorrin Ruihi Shortland; Terry Locke (The Australian Journal of Indigenous Education, 2017)
This article reports on what happened when a Rumaki pūtaiao kaiako (Science) teacher at a New Zealand high school trialled the use of creative narratives with her Year-10 students as a way of developing their understanding of the human digestive system. These students were members of the school's Māori immersion unit, and creative narratives were in part utilised as a bridge between science discourse and the cultural knowledges these students brought to their learning. In this case study, students developed ‘Tomato Pip’ narratives through four versions, which told the story of a tomato pip travelling through the human digestive system. Word-count data based on these versions and from a summative test were analysed and correlations found between test scores and three categories of word-count total (total words, total science words and total discrete science words). A discourse analysis of one student's narratives identified two distinct voices in these texts: the personal narrator and the emerging biologist. Questionnaire and focus-group data indicated that the use of creative narratives was both motivational to these students and effective as a bridge into science discourse mastery. It is argued that the findings have implications for disciplinary literacy theory, Indigenous education and science instruction.